Ornament and preparation method thereof, automotive interior trim part and vehicle

By using core-shell structure nanomaterial cladding on automotive decorations, the problem of insufficient electromagnetic interference and electromagnetic wave absorption performance is solved, and the effect of improving vehicle safety and lightweight is achieved, while also having antibacterial and flame retardant properties.

CN119777149APending Publication Date: 2025-04-08BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411642364.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The electrification and intelligence of electronics in cars lead to electromagnetic interference, affecting the safety of occupants and electronic components. At the same time, existing decorations lack electromagnetic wave absorption performance.

Method used

A core-shell structure nanomaterial including metal nanowires is used as a cladding layer and coated on the substrate to form a decorative object by drying, thereby improving its electromagnetic wave absorption performance.

Benefits of technology

The electromagnetic wave absorption capacity of the decoration is realized, ensuring the vehicle is lightweight while improving safety, and it has antibacterial and flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119777149A_ABST
    Figure CN119777149A_ABST
Patent Text Reader

Abstract

The invention provides an ornament and a preparation method thereof, an automobile interior trim part and a vehicle, and belongs to the technical field of automobile parts, and the ornament comprises a base material and a coating layer. The coating layer coats the base material; wherein the coating layer comprises a core-shell structure nanometer material, and the core-shell structure nanometer material comprises a metal nanowire. The ornament provided by the embodiment of the invention has good electromagnetic wave absorption capacity, and after the ornament is applied to the vehicle, the safety can be improved while the light weight of the vehicle can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of vehicle parts, and in particular to a decorative article and a preparation method thereof, an automobile interior decoration part, and a vehicle. Background Art

[0002] The electronic electrification and intelligence of automobiles have greatly improved people's car-driving experience, but the highly integrated electronic devices and high-frequency switches in the vehicle will generate a large amount of electromagnetic interference during operation, which will have adverse effects on the passengers in the car and the corresponding electronic components.

[0003] Automobile decorations are widely used in the interior and exterior decoration of vehicles, and have characteristics such as lightweight. With the development of lightweight and intelligent automobiles, if the decorations can be endowed with electromagnetic wave absorption, flame retardancy and antibacterial properties, their application potential in automobile safety and lightweight will be significantly improved. However, in the relevant technologies, there is little research on electromagnetic wave absorption performance. Summary of the invention

[0004] The embodiments of the present application provide a decoration and a preparation method thereof, an automobile interior decoration part, and a vehicle. The decoration has electromagnetic wave absorption performance, which can ensure the lightweight of the vehicle while improving safety.

[0005] In order to achieve the above object, according to a first aspect of the present application, a decorative object is provided, comprising:

[0006] Base material;

[0007] The coating layer covers the base material;

[0008] Wherein, the coating layer includes core-shell structure nanomaterials, and the core-shell structure nanomaterials include metal nanowires.

[0009] Optionally, the metal nanowires include at least one of silver nanowires and copper nanowires.

[0010] Optionally, the core-shell structured nanomaterial further includes an organic shell layer, and the organic shell layer is coated on the surface of the metal nanowire.

[0011] Optionally, the organic shell layer comprises a borate polymer shell layer.

[0012] Optionally, the borate polymer in the borate polymer shell layer is formed by polymerization of polymerization monomers; wherein the polymerization monomers include a compound containing a catechol group and a compound containing a phenylboronic acid group.

[0013] Optionally, the structural formula of the compound containing a catechol group is as shown in Formula I to Formula III:

[0014]

[0015] Optionally, the structural formula of the compound containing phenylboronic acid group is as shown in Formula IV to Formula VI:

[0016]

[0017] Optionally, the substrate includes a fabric layer, and the covering layer covers the fabric layer.

[0018] According to a second aspect of the present application, a method for preparing a decoration is also provided, which is used to prepare the decoration as described above, comprising:

[0019] Providing core-shell structure nanomaterials;

[0020] Dispersing the core-shell structure nanomaterial into the pre-crosslinking solution to obtain a core-shell structure nanomaterial solution;

[0021] The core-shell structure nano material solution is coated on a substrate and dried to obtain a decoration.

[0022] Optionally, the mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 2%-15%.

[0023] Optionally, coating the core-shell structure nanomaterial solution on a substrate comprises:

[0024] The substrate is immersed in the core-shell structure nanomaterial solution for 0.5h-2h.

[0025] Optionally, the pre-crosslinking solution includes at least one of a glutaraldehyde-crosslinked polyvinyl alcohol solution, a glutaraldehyde-crosslinked chitosan solution, and a glutaraldehyde-crosslinked polyethyleneimine solution.

[0026] Optionally, the method for preparing the core-shell structured nanomaterial comprises:

[0027] dispersing the metal nanowires in a solvent to obtain a metal nanowire solution;

[0028] Adding a first polymerization monomer solution into the metal nanowire solution and reacting the solution to obtain a first mixed solution;

[0029] Adding a second polymerization monomer solution into the first mixed solution and reacting the mixture to obtain a second mixed solution;

[0030] The second mixed solution is subjected to solid-liquid separation and the separated solid matter is dried to obtain a core-shell structure nanomaterial.

[0031] Optionally, the metal nanowires include at least one of silver nanowires and copper nanowires.

[0032] Optionally, the first polymerization monomer solution includes a compound containing a catechol group, and the second polymerization monomer solution includes a compound containing a phenylboronic acid group.

[0033] Optionally, in the metal nanowire solution, the concentration of the metal nanowires is 0.5 mg / mL-20 mg / mL.

[0034] Optionally, in the first polymerization monomer solution, the concentration of the compound containing a catechol group is 1 mg / mL-20 mg / mL.

[0035] Optionally, in the second polymerization monomer solution, the concentration of the compound containing phenylboronic acid groups is 1 mg / mL-20 mg / mL.

[0036] Optionally, the solvent includes at least one of ethanol and methanol.

[0037] Optionally, the first polymerization monomer solution is added to the silver nanowire solution, and the reaction is stirred for 2 h to 4 h.

[0038] Optionally, the second polymerization monomer solution is added to the first mixed solution, and the mixture is stirred and reacted for 2 h to 4 h.

[0039] According to a third aspect of the present application, there is also provided an automobile interior decoration part, comprising the decoration as described above, and / or the decoration made by the method for making the decoration as described above.

[0040] According to a fourth aspect of the present application, a vehicle is also provided, comprising the automobile interior component as described above.

[0041] The decorative article provided in the embodiment of the present application includes a substrate and a coating layer, and the coating layer is coated on the substrate. The coating layer includes a core-shell structure nanomaterial, and the core-shell structure nanomaterial includes a metal nanowire. Among them, the metal nanowire is a nanoscale material with excellent electrical conductivity. When electromagnetic waves interact with metal nanowires, the high electrical conductivity of the metal nanowires can cause the electromagnetic waves to generate current on its surface and inside, and then convert it into other forms of energy to achieve the absorption of electromagnetic waves. That is, the decorative article provided in the embodiment of the present application has good electromagnetic wave absorption ability. After being applied to vehicles, it can ensure the lightweight of the vehicle while improving safety.

[0042] Other features and advantages of the present application will be described in detail in the subsequent specific implementation section. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0044] In order to more completely understand the present application and its beneficial effects, the following description will be given in conjunction with the accompanying drawings, wherein the same figure numbers represent the same parts in the following description.

[0045] Figure 1 This is a Fourier transform infrared spectrum analysis diagram of the core-shell structure nanomaterial provided in Example 1 of the present application;

[0046] Figure 2 It is a transmission electron microscope and energy dispersive X-ray spectroscopy analysis diagram of the silver nanowires and core-shell structured nanomaterials provided in Example 1 of the present application. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0048] In the first aspect, the embodiment of the present application provides a decorative article, including a substrate and a coating layer. The coating layer includes a core-shell structure nanomaterial, and the core-shell structure nanomaterial includes a metal nanowire. Among them, the metal nanowire is a nanoscale material with excellent conductivity. When electromagnetic waves interact with metal nanowires, the high conductivity of the metal nanowires can cause electromagnetic waves to generate current on its surface and inside, and then convert it into other forms of energy to achieve absorption of electromagnetic waves. Therefore, the decorative article provided by the embodiment of the present application has good electromagnetic wave absorption ability. After being applied to vehicles, it can ensure the lightweight of the vehicle while improving safety.

[0049] In some embodiments, the metal nanowires include at least one of silver nanowires and copper nanowires. Silver nanowires and copper nanowires have excellent electrical conductivity and better electromagnetic wave absorption performance. Silver nanowires can release silver ions and combine with negative charges on bacterial cell walls to destroy the cell structure of bacteria, causing bacterial death. Nanoscale silver nanowires can also penetrate the cell walls of bacteria and directly act on the inside of bacteria to enhance the antibacterial effect. Copper nanowires can attack bacterial cell membranes, nucleic acids and enzymes, destroy cell proteins, thereby causing bacterial death or loss of division and proliferation ability, and have antibacterial properties.

[0050] It is understandable that the metal nanowires may also be gold nanowires or other metal nanowires with good conductive properties.

[0051] In some embodiments, the core-shell structure nanomaterial further includes an organic shell layer, which is coated on the surface of the metal nanowire. The organic shell layer is coated on the surface of the metal nanowire, which can protect the metal nanowire and ensure the stability of the core-shell structure nanowire material in the coating layer.

[0052] In some embodiments, the organic shell layer includes a borate polymer shell layer. The borate polymer shell layer has boron atoms and amine functional groups, and can also interact with components on the bacterial cell wall to destroy the bacterial cell structure, thereby achieving an antibacterial effect. The borate polymer shell layer contains phosphorus, nitrogen and boron elements that can capture free radicals in the condensed phase and gas phase to promote the carbonization of the material, so that it absorbs a large amount of heat during the combustion process and reduces the combustion temperature. The borate polymer shell layer also produces a large amount of water vapor and inert gas during the combustion process, thereby diluting the combustible gas to achieve a flame retardant effect.

[0053] In addition to the above-mentioned core-shell nanomaterials, the metal nanowires or organic shells in the core-shell nanomaterials can also be replaced to form composite materials with corresponding functions. For example, the organic shell can be replaced, such as by nitrogen heterocyclic compounds with stronger coordination ability, or by introducing fluorine or silicon elements with low surface energy to improve hydrophobicity, or by introducing phosphorus elements to enhance flame retardancy, etc. Metal nanowires can be replaced by boron nitride with good thermal conductivity, graphene with good electrical conductivity, or gold nanoparticles with good light energy performance.

[0054] In some embodiments, the borate polymer in the borate polymer shell layer is formed by polymerizing monomers, wherein the polymerizing monomers include a compound containing a catechol group and a compound containing a phenylboronic acid group.

[0055] Among them, the compound containing catechol groups can be combined with metal nanowires through surface hydrogen bonds, and the compound containing catechol groups and the compound containing phenylboronic acid groups can be assembled under the drive of BN coordination to form a borate polymer shell on the surface of the metal nanowire, generating a core-shell structure nanomaterial with a core-shell structure. In addition, the process of forming a borate polymer shell by reacting and polymerizing the compound containing catechol groups and the compound containing phenylboronic acid groups has mild reaction conditions, does not require harsh conditions such as high temperature and high pressure, and can achieve self-assembly.

[0056] In some embodiments, the compounds containing catechol groups have structural formulas as shown in Formula I to Formula III:

[0057]

[0058] The phosphorus element in the compounds shown in Formula I to Formula III can decompose at high temperature to produce phosphorus-containing free radicals and phosphoric acid-containing radicals to promote further carbonization of the matrix and interrupt the free radical reaction of combustion, while the nitrogen element can decompose at high temperature to produce flame-retardant inert gas to dilute the combustibles. In addition, the nitrogen element in the compound mainly appears in the form of secondary amine groups, which can be beneficial to the coordination of BN to further promote the formation of borate polymers and more easily interact with bacterial cell walls in terms of antibacterial properties, thereby improving the antibacterial properties. The catechol group has good affinity with various surfaces through its strong hydrogen bonds, which helps the organic shell layer to be coated on the surface of the inorganic layer.

[0059] In some embodiments, the compounds containing phenylboronic acid groups have structural formulas as shown in Formula IV to Formula VI:

[0060]

[0061] The phenylboronic acid group in the compounds shown in Formula IV to Formula VI can react with the catechol group to form a borate polymer on the surface of the material after dehydration condensation. The nitrogen atom in the Schiff base structure can regulate the formation speed and thickness of the borate polymer through BN coordination. In addition, borate can form boric acid at high temperature, further promoting the carbonization of the matrix at high temperature, and further improving the flame retardant properties of the material. Among them, the compounds shown in Formula V and Formula VI also contain fluorine. The fluorine element has a large electronegativity, and its low polarizability can improve the dielectric properties of the polymer system. In addition, the low surface energy of the fluorine element can also reduce the surface energy of the material, giving the material good hydrophobic properties.

[0062] In some embodiments, the substrate includes a fabric layer, and the covering layer covers the fabric layer.

[0063] The fabric layer has good flexibility and strength, is light in texture and low in cost. By covering the fabric layer with the coating layer, the mechanical strength of the fabric layer can be improved, and the decoration has excellent electromagnetic wave absorption performance.

[0064] Illustratively, the fabric layer may be a cotton fabric layer or a polyester fabric layer.

[0065] According to a second aspect of the present application, a method for preparing a decoration is also provided, which is used to prepare the decoration as described above, comprising:

[0066] Preparation of core-shell structured nanomaterials;

[0067] Dispersing the core-shell structure nanomaterial into the pre-crosslinking solution to obtain a core-shell structure nanomaterial solution;

[0068] The core-shell structure nano material solution is coated on a substrate and dried to obtain a decoration.

[0069] The method for preparing the decoration provided in the embodiment of the present application disperses the core-shell structure nanomaterial into a pre-crosslinked solution to prepare a core-shell structure nanomaterial solution, and then coats the core-shell structure nanomaterial solution on a substrate, and after drying and curing, forms a composite decoration.

[0070] Among them, the pre-crosslinked solution refers to a solution formed by mixing one or more polymers with a crosslinking agent under certain conditions and undergoing a preliminary crosslinking reaction. The polymer molecules in this solution form a preliminary network structure through the action of the crosslinking agent, but have not yet reached a fully crosslinked state. In subsequent processes, further crosslinking can be performed to improve performance.

[0071] In the embodiment of the present application, the substrate is coated with a core-shell structure nanomaterial solution, and the polymer and cross-linking agent initially cross-linked in the pre-cross-linking solution are further cross-linked to form a coating layer with a more stable structure, thereby improving the coating effect.

[0072] For example, the process of coating the core-shell structure nanomaterial solution on the substrate can be carried out by coating, spraying or dipping.

[0073] In some embodiments, the mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 2%-15%. By setting the mass proportion of the core-shell structure nanomaterial within the above range, it can be ensured that the formed coating layer can provide sufficient flame retardancy, antibacterial and electromagnetic wave absorption performance, while helping the core-shell structure nanomaterial to be more evenly dispersed in the core-shell structure nanomaterial solution and reducing cost investment. In addition, setting the mass proportion of the core-shell structure nanomaterial within the above range can also ensure that the core-shell structure nanomaterial solution has a suitable viscosity, so that it has good fluidity, which is convenient for subsequent coating processing of the substrate.

[0074] In some embodiments, coating a substrate with a core-shell structure nanomaterial solution comprises:

[0075] The substrate is immersed in the core-shell structure nanomaterial solution for 0.5h-2h.

[0076] That is, the embodiment of the present application coats the core-shell structure nanomaterial solution on the surface of the substrate by soaking, which is simple in process and improves processing efficiency. The soaking time can be set to 0.5h-2h, so that the core-shell structure nanomaterial solution is fully combined with the substrate to improve the coating effect.

[0077] When the substrate is a fabric layer, part of the core-shell structure nanomaterial solution can enter the pores of the fabric layer by immersion, further improving the mechanical properties, flame retardancy, antibacterial properties and electromagnetic wave absorption properties of the decoration.

[0078] In some embodiments, the pre-crosslinking solution includes at least one of a glutaraldehyde crosslinked polyvinyl alcohol solution, a glutaraldehyde crosslinked chitosan solution, and a glutaraldehyde crosslinked polyethyleneimine solution.

[0079] Among them, in the glutaraldehyde-crosslinked polyvinyl alcohol (PVA) solution, glutaraldehyde and polyvinyl alcohol undergo a cross-linking reaction to form a cross-linked structure, thereby significantly improving the toughness, wear resistance, weather resistance and corrosion resistance of polyvinyl alcohol. The interaction between the cross-linked polyvinyl alcohol molecular chains is enhanced, making the material more stable and able to withstand greater external forces without being easily destroyed.

[0080] In the glutaraldehyde cross-linked chitosan solution, chitosan is a natural polysaccharide with biodegradability and biocompatibility, but it is easily degraded by environmental factors. Glutaraldehyde cross-linking can significantly improve the stability and mechanical strength of chitosan. The interaction between the cross-linked chitosan molecular chains is enhanced, making the material more stable and able to resist enzymatic hydrolysis in the body, thereby extending its service life.

[0081] In the glutaraldehyde cross-linked polyethyleneimine solution, glutaraldehyde, as a commonly used cross-linking agent, can react with the amino groups in the polyethyleneimine molecules to form a cross-linked structure. This cross-linked structure can significantly improve the mechanical properties of polyethyleneimine. Specifically, the interaction between the cross-linked polyethyleneimine molecular chains is enhanced, making the material more stable and able to withstand greater external forces without being easily damaged.

[0082] In some embodiments, preparing a core-shell structured nanomaterial comprises:

[0083] dispersing the metal nanowires in a solvent to obtain a metal nanowire solution;

[0084] Adding the first polymerization monomer solution to the metal nanowire solution to react, thereby obtaining a first mixed solution;

[0085] Adding a second polymerization monomer solution into the first mixed solution and reacting the mixture to obtain a second mixed solution;

[0086] The second mixed solution is subjected to solid-liquid separation and the separated solid matter is dried to obtain a core-shell structure nanomaterial.

[0087] In the preparation method of the core-shell structure nanomaterial provided in the embodiment of the present application, the first polymerization monomer solution is first mixed with the metal nanowire solution to form a first mixed solution, so that the first polymerization monomer is bonded to the surface of the metal nanowire through surface hydrogen bonds, etc., which helps the subsequent assembly reaction to be carried out on the surface of the metal nanowire, thereby forming a dense organic shell layer on the surface of the metal nanowire. Then, the second polymerization monomer solution is added to the first mixed solution, so that the first polymerization monomer and the second polymerization monomer undergo polymerization reaction to form an organic shell layer coated on the surface of the metal nanowire to obtain a second mixed solution. By performing solid-liquid separation on the second mixed solution and drying the separated solid matter, a nanomaterial with a core-shell structure can be obtained.

[0088] The preparation method of the core-shell structure nanomaterial provided in the embodiment of the present application has a simple process and mild reaction conditions, and the obtained core-shell structure nanomaterial has a good coating effect, so that the core-shell structure nanomaterial has good electromagnetic wave absorption performance and mechanical property enhancement and other multi-faceted effects.

[0089] In some embodiments, the metal nanowires include silver nanowires. The effects of the silver nanowires have been described above and will not be repeated here.

[0090] In some embodiments, the first polymerization monomer solution includes a compound containing a catechol group, and the second polymerization monomer solution includes a compound containing a phenylboronic acid group. The compound containing a catechol group and the compound containing a phenylboronic acid group can polymerize to form a borate ester polymer. The specific effects have been described above and will not be repeated here.

[0091] In some embodiments, the concentration of the metal nanowires in the metal nanowire solution is 0.5 mg / mL-20 mg / mL.

[0092] By setting the concentration of metal nanowires within the above range, it is possible to ensure that the metal nanowires are dispersed more evenly, reduce the agglomeration of metal nanowires, and thus improve the coating efficiency and effect. The spacing between metal nanowires in the metal nanowire solution is moderate, which helps to form a coating layer of appropriate thickness on the surface of the metal nanowires during the subsequent coating reaction, thereby improving the uniformity of the coating.

[0093] Illustratively, in the metal nanowire solution, the concentration of the metal nanowires can be 0.5 mg / mL, 1 mg / mL, 3 mg / mL, 5 mg / mL, 7 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL, 18 mg / mL or 20 mg / mL.

[0094] In some embodiments, the concentration of the compound containing a catechol group in the first polymerization monomer solution is 1 mg / mL-20 mg / mL.

[0095] By setting the concentration of the compound containing catechol groups within the above range, it is helpful for the compound containing catechol groups to bind to the surface of the metal nanowires through surface hydrogen bonding, thereby forming a uniform coating layer in the subsequent process, avoiding problems such as sparse distribution caused by too low concentration or uneven accumulation caused by too high concentration. A reasonable concentration range also helps to form a suitable coating layer thickness and improve the performance of the coated core-shell structure nanomaterial.

[0096] In some embodiments, the concentration of the compound containing phenylboronic acid groups in the second polymer solution is 1 mg / mL-20 mg / mL.

[0097] Similarly, by setting the concentration of the compound containing phenylboronic acid groups within the above range, the compound containing phenylboronic acid groups and the compound containing catechol groups are facilitated to undergo an assembly reaction to form a borate ester polymer, thereby forming a uniform coating layer on the surface of the metal nanowire, avoiding problems such as sparse distribution caused by too low concentration or uneven accumulation caused by too high concentration. A reasonable concentration range also helps to form a suitable coating layer thickness and improve the performance of the coated core-shell structure nanomaterial.

[0098] In some embodiments, the solvent includes at least one of ethanol and methanol. Ethanol is a polar solvent, and there is an interaction force between it and the metal nanowires, which helps to improve the dispersion uniformity of the metal nanowires. Ethanol as a solvent can form a stable metal nanowire solution and reduce the agglomeration and precipitation problems of the metal nanowires. Methanol has a small surface tension, and it can improve the dispersion effect of the metal nanowires as a solvent, and it can also ensure the stability of the silver nanowire solution.

[0099] Specifically, ethanol and methanol can be used as solvents alone, or ethanol and methanol can be mixed in a certain ratio and used.

[0100] In some embodiments, the first polymerization monomer solution is added to the metal nanowire solution and stirred for reaction for 2 h to 4 h.

[0101] Stirring can improve the first polymerized monomer to fully contact with the metal nanowire, so that the first polymerized monomer can be bonded to the surface of the metal nanowire through surface hydrogen bonding. By setting the reaction time to 2h-4h, it can be ensured that the first polymerized monomer fully reacts and bonds with the metal nanowire.

[0102] In some embodiments, the second polymerization monomer is added to the first mixed solution and stirred for reaction for 2 h to 4 h.

[0103] Similarly, stirring can improve the second polymerized monomer to fully contact with the metal nanowire combined with the first polymerized monomer, so that the second polymerized monomer can be assembled with the first polymerized monomer. By setting the reaction time to 2h-4h, it can be ensured that the first polymerized monomer and the second polymerized monomer fully react and assemble to form an organic polymer and an organic shell layer.

[0104] According to the third aspect of the present application, there is also provided an automotive interior decoration part, comprising the above-mentioned decoration, and / or the decoration made by the above-mentioned decoration preparation method. The automotive interior decoration part provided in the embodiment of the present application has all the beneficial effects of the above-mentioned decoration, which will not be repeated here.

[0105] According to a fourth aspect of the present application, a vehicle is also provided, comprising the above-mentioned automobile interior decoration. The vehicle provided by the embodiment of the present application has all the beneficial effects of the above-mentioned decoration, which will not be repeated here.

[0106] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.

[0107] Example 1

[0108] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0109] (2) adding 50 mL of a first polymerizable monomer having a concentration of 3 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula I;

[0110]

[0111] (3) adding 50 mL of a second polymerizable monomer having a concentration of 3 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0112]

[0113] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0114] (5) dispersing the core-shell structure nanomaterial into a polyvinyl alcohol solution cross-linked with glutaraldehyde to obtain a core-shell structure nanomaterial solution; wherein the mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 5%;

[0115] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0116] Example 2

[0117] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0118] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula I;

[0119]

[0120] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0121]

[0122] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0123] (5) dispersing the core-shell structure nanomaterial into a polyvinyl alcohol solution cross-linked with glutaraldehyde to obtain a core-shell structure nanomaterial solution; wherein the mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 5%;

[0124] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0125] Example 3

[0126] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0127] (2) adding 50 mL of a first polymerizable monomer having a concentration of 7 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula I;

[0128]

[0129] (3) adding 50 mL of a second polymerizable monomer having a concentration of 7 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0130]

[0131] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0132] (5) dispersing the core-shell structure nanomaterial into a polyvinyl alcohol solution cross-linked with glutaraldehyde to obtain a core-shell structure nanomaterial solution; wherein the mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 5%;

[0133] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0134] Example 4

[0135] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0136] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula I;

[0137]

[0138] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0139]

[0140] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0141] (5) dispersing the core-shell structure nanomaterial into a chitosan solution cross-linked with glutaraldehyde to obtain a core-shell structure nanomaterial solution; wherein the mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 5%;

[0142] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0143] Example 5

[0144] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0145] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula I;

[0146]

[0147] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0148]

[0149] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0150] (5) dispersing the core-shell structured nanomaterial into a glutaraldehyde-crosslinked polyethyleneimine solution to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 5%;

[0151] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0152] Example 6

[0153] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0154] (2) adding 50 mL of a first polymerizable monomer having a concentration of 3 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula II;

[0155]

[0156] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0157]

[0158] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0159] (5) dispersing the core-shell structured nanomaterial into a glutaraldehyde-crosslinked polyethyleneimine solution to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 5%;

[0160] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0161] Example 7

[0162] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0163] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula III;

[0164]

[0165] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0166]

[0167] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0168] (5) dispersing the core-shell structured nanomaterial into a glutaraldehyde-crosslinked polyethyleneimine solution to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 5%;

[0169] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0170] Example 8

[0171] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0172] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula III;

[0173]

[0174] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula IV;

[0175]

[0176] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0177] (5) dispersing the core-shell structured nanomaterial into a glutaraldehyde-crosslinked polyethyleneimine solution to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 5%;

[0178] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0179] Example 9

[0180] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0181] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula III;

[0182]

[0183] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula IV;

[0184]

[0185] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0186] (5) dispersing the core-shell structured nanomaterial into a glutaraldehyde-crosslinked polyethyleneimine solution to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 5%;

[0187] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 2 hours, and then drying to obtain a decorative object.

[0188] Example 10

[0189] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0190] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula III;

[0191]

[0192] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula IV;

[0193]

[0194] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0195] (5) dispersing the core-shell structured nanomaterial into a glutaraldehyde-crosslinked polyethyleneimine solution to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 7%;

[0196] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 2 hours, and then drying to obtain a decorative object.

[0197] Embodiment 11

[0198] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0199] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula III;

[0200]

[0201] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula IV;

[0202]

[0203] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0204] (5) dispersing the core-shell structured nanomaterial into a glutaraldehyde-crosslinked polyethyleneimine solution to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 3%;

[0205] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 2 hours, and then drying to obtain a decorative object.

[0206] Example 12

[0207] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 3 mg / mL;

[0208] (2) adding 50 mL of a first polymerizable monomer having a concentration of 5 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula III;

[0209]

[0210] (3) adding 50 mL of a second polymerizable monomer having a concentration of 5 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula V;

[0211]

[0212] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0213] (5) dispersing the core-shell structured nanomaterial into a glutaraldehyde-crosslinked polyethyleneimine solution to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 3%;

[0214] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 2 hours, and then drying to obtain a decorative object.

[0215] Embodiment 13

[0216] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 0.5 mg / mL;

[0217] (2) adding 50 mL of a first polymerizable monomer having a concentration of 20 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula I;

[0218]

[0219] (3) adding 50 mL of a second polymerizable monomer having a concentration of 20 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0220]

[0221] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0222] (5) dispersing the core-shell structured nanomaterial into a polyvinyl alcohol solution cross-linked with glutaraldehyde to obtain a core-shell structured nanomaterial solution; wherein the mass proportion of the core-shell structured nanomaterial in the core-shell structured nanomaterial solution is 2%;

[0223] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0224] Embodiment 14

[0225] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 20 mg / mL;

[0226] (2) adding 50 mL of a first polymerizable monomer having a concentration of 1 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula I;

[0227]

[0228] (3) adding 50 mL of a second polymerizable monomer having a concentration of 1 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0229]

[0230] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0231] (5) dispersing the core-shell structure nanomaterial into a polyvinyl alcohol solution cross-linked with glutaraldehyde to obtain a core-shell structure nanomaterial solution; wherein the mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 15%;

[0232] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 0.5 h, and drying to obtain a decorative object.

[0233] Embodiment 15

[0234] (1) dispersing the silver nanowires in 100 mL of ethanol to obtain a silver nanowire solution with a silver nanowire concentration of 10 mg / mL;

[0235] (2) adding 50 mL of a first polymerizable monomer having a concentration of 10 mg / mL to the silver nanowire solution, stirring and reacting for 3 hours to obtain a first mixed solution; wherein the first monomer in the first polymerizable monomer is a compound represented by formula I;

[0236]

[0237] (3) adding 50 mL of a second polymerizable monomer having a concentration of 10 mg / mL to the second mixed solution, stirring and reacting for 3 hours to obtain a second mixed solution; wherein the second monomer in the second polymerizable monomer is a compound represented by formula VI;

[0238]

[0239] (4) performing solid-liquid separation on the second mixed solution, and then drying the separated solid matter to obtain a core-shell structured nanomaterial;

[0240] (5) dispersing the core-shell structure nanomaterial into a polyvinyl alcohol solution cross-linked with glutaraldehyde to obtain a core-shell structure nanomaterial solution; wherein the mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 9%;

[0241] (6) Immersing the cotton fabric layer in the core-shell structure nanomaterial solution for 1 hour, and then drying to obtain a decorative object.

[0242] Comparative Example 1

[0243] The cotton fabric layer is immersed in a polyethyleneimine solution cross-linked with glutaraldehyde, treated for 2 hours, and then dried to obtain a decorative object.

[0244] The Fourier transform infrared spectroscopy (FTIR) curve of the core-shell structure nanomaterial obtained in Example 1 was tested and compared with the FTIR standard curves of silver nanowires and borate polymers. Figure 1 As shown, silver nanowire@borate polymer represents the core-shell structured nanomaterial in Example 1, and the FTIR curve of the core-shell structured nanomaterial is consistent with the standard curve of the borate polymer, indicating that the surface of the silver nanowire is coated with a borate polymer shell layer.

[0245] The silver nanowires and the prepared core-shell structure nanomaterials in Example 1 were analyzed by TEM (transmission electron microscope) and EDX (energy dispersive X-ray spectrometer).

[0246] like Figure 2 As shown, Figure 2 Middle (A) and Figure 2 (B) shows the TEM images of silver nanowires and core-shell structured nanomaterials, respectively. It can be seen that the surface of the silver nanowires in the core-shell structured nanomaterials is covered with a coating layer. Figure 2 (C)-(I) are EDX analysis images of core-shell structured nanomaterials. It can be seen that the core-shell structured nanomaterials contain oxygen (O), silver (Ag), phosphorus (P), carbon (C) and nitrogen (N).

[0247] The antibacterial properties, flame retardant properties, tensile properties and electromagnetic wave absorption properties of the decorative articles in Examples 1-15 and Comparative Example 1 were tested. The antibacterial properties were tested according to the method specified in GB / T 20944.3-2008; the flame retardant properties were tested by vertical combustion (UL-94) according to the method specified in ASTM-D 3801; and the tensile properties were tested according to the method specified in GB / T 3929.2-2003.

[0248] The electromagnetic wave absorption performance is tested by the coaxial line method: 40wt% of the test sample (decorations in Examples 1-15 and Comparative Example 1) is mixed with 40wt% of paraffin wax and pressed into a coaxial ring with an outer diameter of 7.0mm, an inner diameter of 3.04mm, and a thickness of 2.0mm for electromagnetic parameter testing. The test instrument model is Agilent's PNA N5224A. The electromagnetic wave absorption performance is evaluated by the reflection loss value (RL), which is calculated according to the transmission line theory, as shown in Formula 1 and Formula 2:

[0249] Z in =Z0(μ r / ε r )1 / 2tanh[j(2πfd / c)(μ r ε r )]1 / 2 formula 1;

[0250] RL=20log10|(Z in -Z0) / (Z in +Z0)| Formula 2;

[0251] Among them, Z0 and Z in Represent free space impedance and standard input impedance respectively; ε r =ε'-jε", ε' and ε" correspond to the real and imaginary parts of the dielectric constant, respectively; μr = μ'-jμ", μ' and μ" correspond to the real and imaginary parts of the magnetic permeability, respectively; f is the microwave frequency; d is the sample thickness; c is the speed of light.

[0252] The test results are shown in Table 1:

[0253] Table 1 Performance test results of the decorations in Examples 1-15 and Comparative Example 1

[0254]

[0255] As can be seen from Table 1, the antibacterial performance, tensile strength, electromagnetic wave absorption performance and flame retardant performance of the decoration obtained in the embodiment of the present application are improved to varying degrees compared with the decoration obtained in Comparative Example 1, indicating that the decoration provided in the embodiment of the present application can significantly improve the comprehensive performance of the decoration by providing a coating layer of nanomaterials with a core-shell structure, while ensuring lightweight and mechanical properties, the decoration realizes electromagnetic wave absorption, flame retardancy, antibacterial and other functions.

[0256] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0257] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0258] The embodiments, implementation methods and related technical features of the present application can be combined and replaced with each other without conflict.

[0259] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A decorative article, characterized in that: include: Base material; A coating layer, wherein the coating layer covers the substrate; Wherein, the coating layer includes a core-shell structure nanomaterial, and the core-shell structure nanomaterial includes metal nanowires.

2. The decorative article according to claim 1, characterized in that: The metal nanowires include at least one of silver nanowires and copper nanowires.

3. The decorative article according to claim 1, characterized in that: The core-shell structure nanomaterial further includes an organic shell layer, and the organic shell layer is coated on the surface of the metal nanowire.

4. The decorative article according to claim 3, characterized in that: The organic shell layer includes a borate polymer shell layer.

5. The decorative article according to claim 4, characterized in that: The borate polymer in the borate polymer shell layer is formed by polymerization of polymerization monomers; wherein the polymerization monomers include a compound containing a catechol group and a compound containing a phenylboronic acid group.

6. The decorative article according to claim 5, characterized in that: The structural formula of the compound containing catechol group is shown in Formula I to Formula III:

7. The decorative article according to claim 5, characterized in that: The structural formula of the compound containing phenylboronic acid group is shown in Formula IV to Formula VI:

8. The decorative article according to any one of claims 1 to 7, characterized in that: The substrate includes a fabric layer, and the covering layer covers the fabric layer.

9. A method for preparing a decoration, used for preparing the decoration according to any one of claims 1 to 8, characterized in that: include: Providing core-shell structure nanomaterials; Dispersing the core-shell structure nanomaterial into a pre-crosslinking solution to obtain a core-shell structure nanomaterial solution; The core-shell structure nano material solution is coated on a substrate and dried to obtain a decoration.

10. The method for preparing a decoration according to claim 9, characterized in that: The mass proportion of the core-shell structure nanomaterial in the core-shell structure nanomaterial solution is 2%-15%.

11. The method for preparing a decoration according to claim 9, characterized in that: The step of coating the core-shell structure nanomaterial solution on a substrate comprises: The substrate is immersed in the core-shell structure nanomaterial solution for 0.5 h to 2 h.

12. The method for preparing a decoration according to claim 9, characterized in that: The pre-crosslinking solution includes at least one of a glutaraldehyde-crosslinked polyvinyl alcohol solution, a glutaraldehyde-crosslinked chitosan solution, and a glutaraldehyde-crosslinked polyethyleneimine solution.

13. The method for preparing a decoration according to claim 9, characterized in that: The method for preparing the core-shell structure nanomaterial comprises: dispersing the metal nanowires in a solvent to obtain a metal nanowire solution; Adding a first polymerization monomer solution to the metal nanowire solution to react, thereby obtaining a first mixed solution; Adding a second polymerization monomer solution to the first mixed solution and reacting the mixture to obtain a second mixed solution; The core-shell structure nanomaterial is obtained by subjecting the second mixed solution to solid-liquid separation and drying the separated solid matter.

14. The method for preparing a decoration according to claim 13, characterized in that: The metal nanowires include at least one of silver nanowires and copper nanowires.

15. The method for preparing a decoration according to claim 13, characterized in that: The first polymerization monomer solution includes a compound containing a catechol group, and the second polymerization monomer solution includes a compound containing a phenylboronic acid group.

16. The method for preparing a decoration according to claim 15, characterized in that: In the metal nanowire solution, the concentration of the metal nanowires is 0.5 mg / mL-20 mg / mL.

17. The method for preparing a decoration according to claim 15, characterized in that: In the first polymerization monomer solution, the concentration of the compound containing a catechol group is 1 mg / mL-20 mg / mL.

18. The method for preparing a decoration according to claim 15, characterized in that: In the second polymerization monomer solution, the concentration of the compound containing phenylboronic acid groups is 1 mg / mL-20 mg / mL.

19. The method for preparing a decoration according to claim 13, characterized in that: The solvent includes at least one of ethanol and methanol.

20. The method for preparing a decoration according to claim 13, characterized in that: The first polymerization monomer solution is added to the metal nanowire solution, and the mixture is stirred and reacted for 2 h to 4 h.

21. The method for preparing a decoration according to claim 13, characterized in that: The second polymerization monomer solution is added to the first mixed solution, and the mixture is stirred for reaction for 2 h to 4 h.

22. An automotive interior component, characterized in that: The invention comprises the decoration according to any one of claims 1 to 8, and / or the decoration made by the method for making the decoration according to any one of claims 9 to 21.

23. A vehicle, characterized in that: Comprising the decorative article as described in claims 1-8, and / or, the automobile interior decoration part as described in claim 22.